Mechanisms of exercise for diabetic neuropathic pain - Jing Luo; Jing Luo; Hui-Qi Zhu; Bo Gou; Yi-Li Zheng (Frontiers in Aging Neuroscience, 2022)
Diabetic neuropathic pain (DNP) is a common disease that affects the daily lives of diabetic patients, and its incidence rate is very high worldwide. At present, drug and exercise therapies are common treatments for DNP. Drug therapy has various side effects. In recent years, exercise therapy has received frequent research and increasing attention by many researchers. Currently, the treatment of DNP is generally symptomatic. We can better select the appropriate exercise prescription for DNP only by clarifying the exercise mechanism for its therapy. The unique pathological mechanism of DNP is still unclear and may be related to the pathological mechanism of diabetic neuropathy. In this study, the mechanisms of exercise therapy for DNP were reviewed to understand better the role of exercise therapy in treating DNP.